Faunal diversity and taxonomic keys of dragonflies in South India (Zoological Records and Reviews, 2022)
Dragonflies and damselflies (Order Odonata) are among the most widely used freshwater bioindicators globally, owing to their complex aquatic larval stage, sensitivity to water quality and habitat condition, and well-developed taxonomy. South India, encompassing the states of Tamil Nadu, Kerala, Karnataka, Andhra Pradesh, and Telangana, harbours one of the most diverse odonate faunas in Asia, with the Western Ghats recognised as a global centre of Odonata endemism.Despite this significance, comprehensive taxonomic inventories and functional identification keys for South Indiandragonflies remain outdated or regionally incomplete. This study presents a systematic faunal survey of dragonflies(Anisoptera) from 68 freshwater habitats across South India, conducted between 2019 and 2021, documenting 186dragonfly species from 68 genera and 11 families. Forty-two species represent new state records, and 8 are putative newspecies pending formal description. The families Libellulidae (84 species) and Gomphidae (38 species) dominate theregional fauna. Species richness is highest in the Western Ghats foothill streams (mean 64.8 species per site) anddeclines sharply in degraded agricultural water bodies (mean 18.4 species per site). Water quality parameters, riparianvegetation cover, and stream gradient are the strongest predictors of odonate species richness. Updated dichotomousidentification keys to all 186 species are provided, with diagnostic illustrations for 48 species. Conservation assessmentsindicate that 34 species qualify as Threatened under IUCN criteria.
Keywords: taxonomic key; Gomphidae; Libellulidae; species richness; freshwater bioindicators; Western Ghats; South India; dragonflies; Anisoptera; Odonata